(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Evidence-based practice (EBP) is a cornerstone of modern healthcare, ensuring that the best available evidence to achieve optimal patient outcomes informs clinical decision-making. Despite its recognized importance, implementing EBP in nursing practice remains a challenge due to various factors such as organizational culture, resource limitations, and individual readiness among nurses. Understanding these factors is crucial for developing effective strategies to promote EBP adoption and integration into nursing care delivery. Aim: The study seeks to elucidate key themes, sub-themes, trends, and explanations surrounding nurses’ readiness, barriers, and facilitators to evidence-based practice implementation. Method: A systematic search of PubMed, CINAHL, Scopus, and Google Scholar databases was conducted to identify relevant research articles published between 2017 and 2021. A total of 4511 articles were initially retrieved, and after screening titles and abstracts for relevance, 10 studies were selected for inclusion in the review. Result: The selected studies provided insights into nurses’ varying levels of readiness for EBP implementation, the influence of organizational culture and leadership support, barriers such as structural deficiencies and limited resources, and facilitators including mentorship and training initiatives. Conclusion: The findings highlight the complex interplay of factors influencing EBP implementation in nursing practice. Addressing competency gaps, fostering a supportive organizational culture, overcoming barriers, and enhancing facilitators are essential steps towards promoting and sustaining evidence-based practice.